2016
DOI: 10.1016/j.ssmph.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of race, socioeconomic status and neighborhood residence upon birth outcomes in a high black infant mortality community

Abstract: This study examined the interrelationship of race and socioeconomic status (SES) upon infant birthweight at the individual and neighborhood levels within a Midwestern US county marked by high Black infant mortality. The study conducted a multi-level analysis utilizing individual birth records and census tract datasets from 2010, linked through a spatial join with ArcGIS 10.0. The maternal population of 2861 Black and White women delivering infants in 2010, residing in 57 census tracts within the county, consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 90 publications
2
24
2
Order By: Relevance
“…Although maternal poverty was linked to 1.7 times greater odds of LBW deliveries, higher-SES Black women in predominantly White areas had the worst outcomes (14.5% LBW). In contrast, high-SES Black women who were residing in predominantly Black neighborhoods had the most desirable outcomes (4.0% LBW) (Kothari et al, 2016). This study showed an interaction between race and SES and also variation in the protective effect of SES across contexts.…”
Section: Introductionmentioning
confidence: 54%
“…Although maternal poverty was linked to 1.7 times greater odds of LBW deliveries, higher-SES Black women in predominantly White areas had the worst outcomes (14.5% LBW). In contrast, high-SES Black women who were residing in predominantly Black neighborhoods had the most desirable outcomes (4.0% LBW) (Kothari et al, 2016). This study showed an interaction between race and SES and also variation in the protective effect of SES across contexts.…”
Section: Introductionmentioning
confidence: 54%
“…There are, however, variations in the effects of SES and SDOH indicators depending on social context and demographic factors [4]. In other terms, the health effects of SES and SDOH indicators such as education depend on race and place, suggesting a complex interplay between race, place, and resources on shaping populations' and individuals' health outcomes [5].…”
Section: Introductionmentioning
confidence: 99%
“…How an SES indicator alters the living conditions and outcomes of populations and individuals may, however, vary across demographic groups [3]. That is, the real-world effects of SES indicators such as education depend on ethnicity, race, and place, suggesting that ethnicity, resources, and place interact with one another in how they alter health and behaviors [4]. For example, the effects of income may depend on what people can purchase and what services people can receive in the exchange of such income [5].…”
Section: Introductionmentioning
confidence: 99%